2011
DOI: 10.1007/s13246-011-0092-2
|View full text |Cite
|
Sign up to set email alerts
|

Validation of image registration and fusion of MV CBCT and planning CT for radiotherapy treatment planning

Abstract: In areas like adaptive therapy, multi-phase radiotherapy, and single fraction palliative treatment or in the treatment of patients with metal implants where megavoltage(MV) CT could be considered as a treatment planning modality, the reduced contrast in the MV CT images could lead to limited accuracy in localization of the structures. This would affect the precision of the treatment. In this study, as an extension our previous work on bespoke MV cone beam CT (MV CBCT), we propose to register the MV CBCT with k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In the future, elastic registration may play a role as well and therefore it is important to evaluate its accuracy. Various methods to validate image registration have been proposed, such as tracking of landmarks (Coselmon et al 2004, Brock et al 2005, Rietzel and Chen 2006, Heath et al 2007, Yin et al 2010, Castillo et al 2009, Gu et al 2010, Nithiananthan et al 2009, Shamir et al 2009, Brock 2010, Gendrin et al 2011, Murphy et al 2011, Gu et al 2011, Pruem et al 2011, Liu et al 2012, check of the alignment of contours (Heath et al 2007, Wijesooriya et al 2008 or overlap of volumes (Klein et al 2009, Hardcastle et al 2012, evaluation of the overlay of corresponding structures in a color wash or a split screen technique (Kessler 2006, Thomas et al 2011 as well as the investigation of the performance on artificially created test cases, where the ground truth on the deformation is known (Wang et al 2005, Schnabel et al 2003, Kybic and Unser 2003, Kashani et al 2007, Li et al 2009, Long et al 2010, Zhong et al 2010, Kirby et al 2011, Chang et al 2010. Szegedi et al 2012 and Szegedi et al 2013 created a real tissue phantom to evaluate image registration in the presence of motion that involves four dimensional hysteresis.…”
Section: Introductionmentioning
confidence: 99%
“…In the future, elastic registration may play a role as well and therefore it is important to evaluate its accuracy. Various methods to validate image registration have been proposed, such as tracking of landmarks (Coselmon et al 2004, Brock et al 2005, Rietzel and Chen 2006, Heath et al 2007, Yin et al 2010, Castillo et al 2009, Gu et al 2010, Nithiananthan et al 2009, Shamir et al 2009, Brock 2010, Gendrin et al 2011, Murphy et al 2011, Gu et al 2011, Pruem et al 2011, Liu et al 2012, check of the alignment of contours (Heath et al 2007, Wijesooriya et al 2008 or overlap of volumes (Klein et al 2009, Hardcastle et al 2012, evaluation of the overlay of corresponding structures in a color wash or a split screen technique (Kessler 2006, Thomas et al 2011 as well as the investigation of the performance on artificially created test cases, where the ground truth on the deformation is known (Wang et al 2005, Schnabel et al 2003, Kybic and Unser 2003, Kashani et al 2007, Li et al 2009, Long et al 2010, Zhong et al 2010, Kirby et al 2011, Chang et al 2010. Szegedi et al 2012 and Szegedi et al 2013 created a real tissue phantom to evaluate image registration in the presence of motion that involves four dimensional hysteresis.…”
Section: Introductionmentioning
confidence: 99%
“…CBCT-guided radiotherapy positioning is influenced by various factors, primarily observer-related differences in judgment, 2,3 the quality of images used for registration, [4][5][6] different registration algorithms, [7][8][9] and the choice of registration regions. [10][11][12] Some studies have emphasized that selecting different regions of interest (ROIs) for online image registration in planning images can lead to varying displacements.…”
Section: Introductionmentioning
confidence: 99%
“…Bissonnette et al 1 confirmed that the verification and adjustment of radiotherapy setup, guided by cone‐beam computed tomography (CBCT), can effectively enhance the geometric accuracy of lung cancer radiotherapy and minimize the external margin of the planning target volume (PTV). The accuracy of CBCT‐guided radiotherapy positioning is influenced by various factors, primarily observer‐related differences in judgment, 2 , 3 the quality of images used for registration, 4 , 5 , 6 different registration algorithms, 7 , 8 , 9 and the choice of registration regions. 10 , 11 , 12 Some studies have emphasized that selecting different regions of interest (ROIs) for online image registration in planning images can lead to varying displacements.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts have been made to overcome this problem using an extended CT number range [6], orthovoltage cone beam CT [7], and megavoltage cone beam CT [8,9]. However these techniques are either uncommon or experimental and are not available in many clinical departments [10].…”
Section: Introductionmentioning
confidence: 99%